Control and Prediction of Solid-State of Pharmaceuticals Experimental and Computational Approaches - Bhardwaj, Rajni Miglani; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This thesis investigates a range of experimental and computational approaches to the discovery of solid forms. It illustrates an inexpensive, practical and accurate way to predict the crystallizability of organic compounds based on molecular structure alone, while also highlighting the molecular factors that inhibit or promote crystallization. Furthermore, readers will gain a better understanding of the key factors underpinning solid-state structure and diversity. A major part of the thesis highlights experimental work carried out on two structurally very similar compounds, while another main section examines the influence of small changes in structure and substituents on solid-state structure and diversity using computational tools including crystal structure prediction, PIXEL calculations, Xpac, Mercury and statistical modelling tools. In closing, the author presents a fast validated method for solid-state form screening using Raman microscopy on multi-well plates to explore the experimental crystallization space.
Introduction -- Aims and Objectives -- Materials and Methods -- Development and Validation of High_Throughput Crystallization and Analysis (HTCAA) Methodology for Physical Form Screening -- Predicting Crystallizability of Organic Molecules using Statistical Modelling Techniques -- Exploring Crystal Structure Landscape of Olanzapine -- Exploring the Physical Form Landscape of Clozapine, Amoxapine and Loxapine -- Conclusions and Further Work.
Keywords: Physical chemistry; Pharmaceutical chemistry; Chemistry, Physical and theoretical; Physical Chemistry; Pharmaceutics; Theoretical Chemistry